A method for preparing a sulfided bulk hydrogenation catalyst

By introducing multifunctional complexing agent and microwave technology, an efficient vulcanized bulk hydrogenation catalyst was prepared, which solved the problems of low utilization rate of existing catalyst active metals and environmental pollution, and achieved efficient hydrodesulfurization and denitrification activities. , meets the refinery's demand for sulfur-free diesel products.

CN116251605BActive Publication Date: 2024-12-20CHINA NAT OFFSHORE OIL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202211729096.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-31
Publication Date
2024-12-20
Estimated Expiration
2042-12-31

AI Technical Summary

Technical Problem

The existing hydrogenation catalysts have low utilization rate of active metals and insufficient mechanical strength during ultra-deep desulfurization. In addition, the traditional preparation methods have environmental pollution problems, making it difficult to meet the refinery's demand for sulfur-free diesel products.

Method used

Using multifunctional complexing agent, hot impregnation, molecular sieve, amorphous silicon-aluminum, adhesive and microwave sensitizer, a high-efficiency vulcanized body-phase hydrogenation catalyst is prepared through ultrasonic dispersion and microwave drying at different frequencies. Improve the dispersion uniformity and utilization of active metals.

Benefits of technology

It improves the hydrodesulfurization and denitrification activity of the catalyst, enhances mechanical strength, reduces production costs, and avoids environmental pollution, meeting the refinery's demand for sulfur-free diesel products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004031398240000061
    Figure BDA0004031398240000061
  • Figure BDA0004031398240000071
    Figure BDA0004031398240000071
Patent Text Reader

Abstract

The invention discloses a method for preparing a vulcanized bulk hydrogenation catalyst. The method includes: first, ammonium dithiocarbamate, nickel salt and / or cobalt salt, hydroxyethylidene diphosphonic acid, hydroxyphosphonoacetic acid and deionized water are mixed, heated and stirred, and then ammonium tetrathiomolybdate and / or ammonium tetrathiotungstate are added, and the obtained sulfur-containing composite active metal precursor impregnation solution is mixed with an adhesive, a microwave sensitizer and a dispersant at a temperature of 50°C to 90°C, and then ultrasonically dispersed, beaten, kneaded, extruded, and then under nitrogen protection, first dried with a microwave having a radiation frequency of 840MHz, and then dried with a microwave having a radiation frequency of 2450MHz, to obtain a vulcanized bulk hydrogenation catalyst. The method of the present invention is efficient and simple, the active metals are evenly dispersed, the synergy between different active metals is good, and the effective utilization rate of the active metals is high, which makes the catalyst more likely to generate a more active II-type Mo(W)-Ni(Co)S active phase, so that the vulcanized bulk hydrogenation catalyst has excellent hydrogenation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a sulfidation type bulk hydrogenation catalyst. Background Art

[0002] At present, crude oil is becoming heavier and inferior, and with the continuous development of the world economy and increasingly stringent environmental regulations, a large amount of light clean fuel needs to be produced. The development and use of ultra-low sulfur or even sulfur-free gasoline and diesel is the trend of clean fuel development worldwide today. The use of traditional hydrodesulfurization catalysts can also achieve deep desulfurization or even ultra-deep desulfurization of diesel by increasing the severity of the reaction, such as increasing the reaction temperature, hydrogen partial pressure, or reducing the reaction space velocity. However, the increase in reaction temperature will lead to a deterioration in product color and a shortened catalyst life, while reducing the space velocity means a reduction in processing volume. For existing hydrogenation units, the design pressure is fixed, and the range of increasing the hydrogen partial pressure is limited. Therefore, currently, the use of catalysts with higher desulfurization activity is one of the important means of deep desulfurization.

[0003] There are sulfur compounds with various structures and different molecular weights in petroleum fractions, but in the ultra-deep desulfurization stage (sulfur content is less than 50μg / g), the main sulfur compounds with substituents such as 4,6-dimethyldibenzothiophene are removed. Since the methyl group adjacent to the sulfur atom creates a steric hindrance between the sulfur atom and the active center of the catalyst, the sulfur atom is not easy to approach the active center of the reaction, resulting in a significant decrease in the reaction rate.

[0004] Traditional supported hydrogenation catalysts are limited by the pore structure of the carrier, and the active metal loading generally does not exceed 30wt%. The number of active centers that supported catalysts can provide is limited. Although the number and type distribution of active centers can be optimized and adjusted, the bottleneck of the number of active centers cannot be broken through, and the space for significantly improving the hydrogenation activity is limited, making it difficult to meet the refinery's demand for producing National V diesel products. The hydrogenation catalyst prepared by the bulk phase method is mostly composed of active metal components, which can get rid of the limitation of metal content, and the proportion of each active component in the catalyst can be arbitrarily adjusted to improve the hydrogenation performance of the catalyst. Because the bulk phase catalyst has excellent hydrogenation activity, it can directly produce sulfur-free diesel products that meet the National V standard without increasing the severity of the device reaction. The original device does not need to be modified, and the processing capacity of the device can be increased, reducing the production cost of the refinery and achieving energy saving and efficiency improvement.

[0005] Bulk hydrogenation catalysts are divided into sulfided bulk hydrogenation catalysts and oxidized bulk hydrogenation catalysts. The preparation process of oxidized bulk catalysts is relatively simple and low-cost, and has been industrially applied. It is mainly prepared by coprecipitation method, mainly based on active metal components, which are usually group VIB metal elements (Mo, W) and group VIII metal elements (Ni). The active metal atoms are interlaced to provide reaction space for reactant molecules. The active metal is exposed on the catalyst surface to provide reactive centers for reactant molecules. Supported catalysts are composed of a mixture of lower activity type I active centers and higher activity type II active centers, while the active centers of bulk catalysts are basically all type II active centers. Bulk catalysts mainly increase the density of active centers on the catalyst to greatly improve their catalytic activity. Chianelli et al. proposed a radial-edge model to explain the generation of active centers of non-supported catalysts. The model calls the edge active sites on the outer edge of MoS2 / WS2 grains radial sites, which provide hydrogenation centers, and the edge active sites on the inner layer of MoS2 / WS2 grains edge sites, which provide hydrogenolysis centers. Therefore, the hydrogenation and hydrogenolysis activities of the catalyst are closely related to the distribution of active sites.

[0006] During the reaction, the reactant molecules react only on the catalyst surface close to them. The active metals on the catalyst surface prepared by the existing co-precipitation method are unevenly dispersed, and the disordered distribution of different hydrogenation active metals causes activity.

[0007] Although the bulk hydrogenation catalyst has a high content of active metals, it is limited by mechanical strength and the easy aggregation of active metals, so a certain amount of binder components needs to be added. Generally, to meet the requirements of mechanical strength, the amount of binder added should be more than 30wt%, or even more. This not only reduces the amount of active metals, but also causes some active metals to enter the bulk phase, making it unable to become a hydrogenation active center, resulting in a low utilization rate of active metals. Therefore, for bulk hydrogenation catalysts, in order to improve the utilization rate of active metals, it is necessary to increase the density of active sites on the catalyst surface, thereby improving the activity of the catalyst.

[0008] The oil refining industry in the 21st century must follow a sustainable development strategy and must pay attention to the principles of economic benefits, environmental protection and resource conservation. Therefore, it is more important to produce bulk catalysts using a preparation method that does not pollute the environment. Most of the existing co-precipitation catalyst preparation technologies use NH3·H2O as a precipitant, which will produce a large amount of wastewater containing ammonia and nitrogen, causing environmental pollution.

[0009] CN1951561A discloses a method for preparing a hydrogenation catalyst by coprecipitation. The catalyst uses active metal Ni and W components and a precipitant to coprecipitate to generate Ni x W y O zThe composite oxide precursor can be added with an aluminum salt solution in the above process, or aluminum hydroxide can be directly added after gelation, and then mixed with MoO3 by slurrying, filtering, molding, and activation to obtain the final catalyst. When the bulk catalyst prepared by this method meets the use requirements of mechanical strength, its surface active site density is low, and the advantages of high-content active metal components cannot be fully utilized, which reduces the utilization rate of active metals and increases the preparation cost of the catalyst.

[0010] CN101306374A discloses a hydrogenation catalyst composition, which is prepared by a coprecipitation method, wherein at least one compound of a Group VIII metal component, at least two compounds of a Group VIB metal component, an organic additive and water are mixed to prepare a mixed solution, an acid or an alkali is used to adjust the pH of the mixed solution to 7 to 11, the mixed solution is placed in a reactor, reacted under a closed condition of room temperature to 250°C for 1 to 24 hours, and then filtered and dried. The catalyst obtained by this method is not subjected to high-temperature roasting, and the final catalyst contains an organic additive. In order to make the mechanical strength of the catalyst meet the use requirements, more adhesive components need to be added, which will make the catalyst surface active and reduce the activity of the catalyst.

[0011] CN101255356A discloses a method for preparing a non-supported catalyst, which uses a urea melting reaction technology to mix a precursor containing active metals of Group VIII and Group VIB with urea and react them in a urea melting state, remove excess urea, and obtain catalyst particles, which can be molded by adding a binder. In this method, urea is added as a precipitant, and after the reaction, it is necessary to heat to remove excess urea, and then add a binder for molding. In this method, the addition of the binder still has the problem that the density of active sites on the catalyst surface is low.

[0012] The hydrogenation active centers of hydrogenation catalysts prepared by the bulk phase method are on the surface of the catalyst pores that are accessible to the reactant molecules. Although such catalysts have a high content of active metals, not all active metals can become hydrogenation active centers. Therefore, how to improve the distribution of hydrogenation active metals so that more active metals are distributed on the pore surface to form hydrogenation active centers, increase the active center density on the surface of the bulk phase catalyst, and improve the utilization rate of the hydrogenation active metal components are currently important research topics.

[0013] The bulk hydrogenation catalyst disclosed in CN102049265A adds ammonium bicarbonate during the co-precipitation process, and the bulk hydrogenation catalyst disclosed in CN102451703A adds carbon dioxide during the co-precipitation process to generate carbonates or bicarbonates. The above methods all utilize a certain amount of gas released during the roasting process. Under the impact of the gas, the pore volume and specific surface area of ​​the catalyst are increased, so that more metal active sites are exposed on the surface of the catalyst. However, this method will cause part of the pores to collapse, the pore distribution to be diffuse, the mechanical strength to be reduced, and the active metal to be locally aggregated, so that the exposed metal active sites are limited.

[0014] In the ultra-deep hydrodesulfurization reaction environment of distillate oil, the organic nitrogen-containing compounds present in the distillate oil have a significant inhibitory effect on the hydrodesulfurization reaction, and the hydrodesulfurization activity decreases with the increase of nitrogen content in the feedstock. This is because the nitrogen-containing compounds and sulfides in the distillate oil compete for adsorption on the active sites of the catalyst. The adsorption capacity of nitrides is strong, occupying the active sites on the catalyst, making it difficult for sulfides to approach, inhibiting the hydrodesulfurization reaction. Therefore, when treating heavy diesel with high nitrogen content to produce ultra-low sulfur products, the catalyst needs to have excellent hydrodenitrification activity. The hydrodenitrification activity of the catalyst is improved. After the nitrogen content is reduced, the nitrogen compounds that compete with sulfides for adsorption are reduced, and sulfides are more easily and more adsorbed on the active sites of the catalyst, promoting the hydrodesulfurization reaction. Therefore, improving the hydrodenitrification activity of the catalyst plays an extremely important role in improving the ultra-deep hydrodesulfurization activity of the bulk catalyst. Summary of the invention

[0015] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art. By introducing a multifunctional complexing agent, combining hot impregnation, molecular sieves, amorphous silicon aluminum, adhesives, microwave sensitizers and dispersant mixing, ultrasonic dispersion and microwave drying treatment of different frequencies under nitrogen protection, a method for preparing a sulfide-type bulk hydrogenation catalyst with high efficiency and simplicity, uniform dispersion of active metals, good synergy between different active metals, high effective utilization rate of active metals, high proportion of type II Mo(W)-Ni(Co)S active phase and excellent performance is provided.

[0016] The invention discloses a preparation method of a sulfurized bulk hydrogenation catalyst, comprising: firstly mixing ammonium dithiocarbamate, nickel salt and / or cobalt salt, hydroxyethylidene diphosphonic acid, hydroxyphosphonoacetic acid and a certain amount of deionized water, heating and stirring, then adding ammonium tetrathiomolybdate and / or ammonium tetrathiotungstate to obtain a sulfur-containing composite active metal precursor impregnation solution, mixing the sulfur-containing composite active metal precursor impregnation solution with an adhesive, a microwave sensitizer and a dispersant at a temperature of 50°C to 90°C, then ultrasonically dispersing, beating, kneading and extruding, and then drying with a microwave having a radiation frequency of 840 MHz and controlling the microwave drying temperature to be 100 to 120°C under nitrogen protection, and then drying with a microwave having a radiation frequency of 2450 MHz and controlling the microwave drying temperature to be 350 to 600°C to obtain a sulfurized bulk hydrogenation catalyst; the molar amount of the ammonium dithiocarbamate used is 50% to 300% of the molar amount of the nickel salt and / or the cobalt salt, preferably 100% to 150%.

[0017] In the method for preparing the sulfided bulk hydrogenation catalyst of the present invention, the nickel salt and / or cobalt salt is selected from one or more of basic carbonates, nitrates and acetates, preferably basic carbonates.

[0018] In the method for preparing the sulfidation type bulk hydrogenation catalyst of the present invention, the binder is preferably one or more of aluminum sol, silica sol, aluminum silicate and silica-alumina gel.

[0019] In the method for preparing the sulfidation type bulk hydrogenation catalyst of the present invention, the microwave sensitizer is preferably one or more of Fenton's reagent, activated carbon, graphite, conductive carbon black, semi-conductive carbon black and carbon fiber sensitizer.

[0020] In the preparation method of the vulcanized bulk hydrogenation catalyst of the present invention, the dispersant is one or more of alkylamide compounds, polycarboxylic acids, oligomers composed of polycarboxylic acids and polyamines, triethylhexyl phosphoric acid, alkyl sulfates, alkyl sulfonates, methyl amyl alcohol, cellulose derivatives, polyacrylamide, guar gum, fatty acid polyethylene glycol esters, silicates, polyethylene wax, oxidized polyethylene wax, polyethylene glycol, polyvinyl alcohol, polypropylene alcohol, methyl cellulose, carboxymethyl cellulose, isopropanol, sec-butyl alcohol, levulinic acid esters, hydrolyzed polymaleic anhydride (HPMA), ethylene-acrylic acid copolymers, ethylene-vinyl acetate copolymers, metal salts of higher fatty acids, fatty acid compounds, aliphatic amide compounds, ester compounds, paraffin, polyurethane, fatty acid glyceride, fatty acid sorbitan, Tween, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and acrylic polymers (such as LBD-1 dispersant), and the amount used is 1wt% to 20wt% of the weight of the carrier component.

[0021] In the method for preparing the sulfidation type bulk hydrogenation catalyst of the present invention, the ultrasonic time is 5 to 30 minutes.

[0022] In the preparation method of the sulfided bulk hydrogenation catalyst of the present invention, the 840 MHz microwave drying time is 10 to 30 minutes; the 2450 MHz microwave drying time is 20 to 120 minutes.

[0023] In the preparation method of the sulfided bulk hydrogenation catalyst of the present invention, the sulfided hydrocracking catalyst contains 30wt% to 60wt% of molybdenum and / or tungsten, and 1wt% to 15wt% of cobalt and / or nickel, based on the weight of the final catalyst.

[0024] The present invention further provides a sulfided bulk hydrogenation catalyst prepared by the above preparation method.

[0025] Compared with the prior art, the present invention has the following beneficial effects: by introducing a multifunctional complexing agent, combining hot impregnation, adhesive, microwave sensitizer and dispersant mixing, ultrasonic dispersion and microwave drying treatment of different frequencies under nitrogen protection, a method for preparing a sulfide-type bulk hydrogenation catalyst with high efficiency and simplicity, uniform dispersion of active metals, good synergy between different active metals, high effective utilization rate of active metals, high ratio of II-type Mo(W)-Ni(Co)S active phase and excellent performance is provided.

[0026] The sulfide-type bulk hydrogenation catalyst prepared by the method of the present invention is mainly used in the deep hydrogenation process and is suitable for treating one or more of various oil products such as vacuum gas oil, thermally refined gas oil, catalytically refined gas oil, catalytically refined circulating oil, coking gas oil, deasphalted oil, etc. The raw materials are usually hydrocarbons with a boiling point of 180 to 700°C. DETAILED DESCRIPTION

[0027] The technical features of the present invention are described in detail below with specific embodiments, but the embodiments do not limit the protection scope of the present invention.

[0028] The specific preparation steps of the present invention are as follows: firstly, ammonium dithiocarbamate, nickel salt and / or cobalt salt, hydroxyethylidene diphosphonic acid, hydroxyphosphonoacetic acid and a certain amount of deionized water are mixed, heated and stirred, then ammonium tetrathiomolybdate and / or ammonium tetrathiotungstate are added, the obtained sulfur-containing composite active metal precursor impregnation solution is mixed with a binder, a microwave sensitizer and a dispersant at a temperature of 50°C to 90°C, then ultrasonically dispersed, slurried, kneaded, extruded into strips, and then, under nitrogen protection, firstly dried with microwaves having a radiation frequency of 840 MHz, and the microwave drying temperature is controlled to be 100 to 120°C, and then dried with microwaves having a radiation frequency of 2450 MHz, and the microwave drying temperature is controlled to be 350 to 600°C, to obtain a sulfurized bulk hydrogenation catalyst.

[0029] Embodiment 1:

[0030] 50 g of ammonium dithiocarbamate, 25 g of basic nickel carbonate, 10 g of hydroxyethylidene diphosphonic acid, 10 g of hydroxyphosphonoacetic acid and 70 g of deionized water were mixed, heated and stirred at 90° C., and then 120 g of ammonium tetrathiomolybdate was added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 50 g of aluminum sol (solid content mass fraction was 35%), 3 g of activated carbon and 5 g of carboxymethyl cellulose at 90° C., and then ultrasonically dispersed for 8 minutes, beaten, kneaded, and extruded into strips. Then, under nitrogen protection, first dried with microwaves at a radiation frequency of 840 MHz, a microwave drying temperature of 110° C., and a drying time of 20 minutes, and then dried with microwaves at a radiation frequency of 2450 MHz, a microwave drying temperature of 450° C., and a drying time of 40 minutes to obtain a sulfurized bulk hydrogenation catalyst 1.

[0031] Embodiment 2:

[0032] 10 g of ammonium dithiocarbamate, 20 g of nickel nitrate, 10 g of nickel acetate, 5 g of hydroxyethylidene diphosphonic acid, 5 g of hydroxyphosphonoacetic acid and 50 g of deionized water were mixed, heated and stirred at 80°C, and then 100 g of ammonium tetrathiotungstate was added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 100 g of silica sol (solid content mass fraction of 35%), 2 g of Fenton reagent and 1 g of polyethylene glycol at 80°C, and then ultrasonically dispersed for 5 minutes, beaten, kneaded, and extruded into strips. Then, under nitrogen protection, first dried with microwaves with a radiation frequency of 840 MHz, a microwave drying temperature of 120°C, and a drying time of 10 minutes, and then dried with microwaves with a radiation frequency of 2450 MHz, a microwave drying temperature of 600°C, and a drying time of 20 minutes to obtain a sulfurized bulk hydrogenation catalyst 2.

[0033] Embodiment 3:

[0034] 15 g of ammonium dithiocarbamate, 15 g of nickel nitrate, 13 g of nickel acetate, 3 g of hydroxyethylidene diphosphonic acid, 7 g of hydroxyphosphonoacetic acid and 50 g of deionized water were mixed, heated and stirred at 70°C, and then 60 g of ammonium tetrathiomolybdate and 40 g of ammonium tetrathiotungstate were added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 90 g of aluminum silicate gel (solid content mass fraction was 35%), 0.5 g of graphite and 8 g of Tween at 70°C, and then ultrasonically dispersed for 15 minutes, beaten, kneaded, and extruded into strips. Then, under nitrogen protection, first dried with microwaves at a radiation frequency of 840 MHz, a microwave drying temperature of 100°C, and a drying time of 30 minutes, and then dried with microwaves at a radiation frequency of 2450 MHz, a microwave drying temperature of 350°C, and a drying time of 120 minutes to obtain a sulfurized bulk hydrogenation catalyst 3.

[0035] Embodiment 4:

[0036] 20 g of ammonium dithiocarbamate, 20 g of nickel nitrate, 10 g of cobalt nitrate, 5 g of hydroxyethylidene diphosphonic acid, 7 g of hydroxyphosphonoacetic acid and 40 g of deionized water were mixed, heated and stirred at 50° C., and then 80 g of ammonium tetrathiomolybdate was added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 50 g of silica sol (solid content mass fraction of 35%), 50 g of silica-alumina gel (solid content mass fraction of 35%), 2 g of carbon fiber sensitizer and 8 g of gul gum at 50° C., and then ultrasonically dispersed for 30 minutes, beaten, kneaded, and extruded into strips. Then, under nitrogen protection, first dried with microwaves at a radiation frequency of 840 MHz, a microwave drying temperature of 120° C., and a drying time of 30 minutes, and then dried with microwaves at a microwave radiation frequency of 2450 MHz, a microwave drying temperature of 500° C., and a drying time of 60 minutes to obtain a sulfurized bulk hydrogenation catalyst 4.

[0037] Comparative Example 1:

[0038] 20 g of nickel nitrate, 10 g of cobalt nitrate, 10 g of citric acid and 40 g of deionized water were mixed, stirred at 30°C for 1 hour, and then 100 g of ammonium tetrathiomolybdate was added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 100 g of silica sol (solid content mass fraction of 35%) at 30°C, and then slurried, kneaded and extruded into strips. Under nitrogen protection, it was calcined at 500°C for 5 hours to obtain bulk hydrogenation catalyst A.

[0039] Table 1 Physicochemical properties of the catalysts obtained in the examples and comparative examples

[0040]

[0041] It can be seen from Table 1 that the specific surface area, pore volume and strength of the sulfided bulk hydrogenation catalyst prepared according to the present invention are superior to those of the bulk hydrogenation catalyst prepared according to the conventional method.

[0042] The above-mentioned sulfided bulk hydrogenation catalyst 1, sulfided bulk hydrogenation catalyst 2, sulfided bulk hydrogenation catalyst 3, sulfided bulk hydrogenation catalyst 4 and bulk hydrogenation catalyst A of the present invention were subjected to activity evaluation test on a 100 mL small-scale hydrogenation device. The properties of the raw oil used are shown in Table 1. The evaluation conditions are: hydrogen partial pressure of 15 MPa, hydrogen-oil volume ratio of 1000:1, reaction temperature of 360°C, liquid hourly volume space velocity of 1.5 h -1 , catalyst evaluation results.

[0043] Table 1 Main properties of crude oil

[0044] project data <![CDATA[Density (at 20 °C), g / cm 3 > 0.9125 Distillation range, ℃ IBP / 10% / 50% / 90% / 95% / EBP 309 / 426 / 474 / 526 / 537 / 553 S, μg / g 11650 N, μg / g 621

[0045] Table 2 The activity of the catalyst samples is expressed as relative hydrodesulfurization rate (with the comparative bulk hydrogenation catalyst A as 100)

[0046]

[0047] It can be seen from the above results that the sulfided bulk hydrogenation catalyst obtained by the method of the present invention has better hydrodesulfurization and hydrodenitrogenation activities.

[0048] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the invention may be modified or replaced by equivalents without departing from the scope of the technical solutions of the present invention, which should all be covered by the scope of the claims of the present invention.

Claims

1. A method for preparing a sulfided bulk hydrogenation catalyst, characterized in that: The preparation method comprises: firstly mixing ammonium dithiocarbamate, nickel salt and / or cobalt salt, hydroxyethylidene diphosphonic acid, hydroxyphosphonoacetic acid and a certain amount of deionized water, heating and stirring, then adding ammonium tetrathiomolybdate and / or ammonium tetrathiotungstate to obtain a sulfur-containing composite active metal precursor impregnation solution, mixing the sulfur-containing composite active metal precursor impregnation solution with an adhesive, a microwave sensitizer and a dispersant at a temperature of 50° C. to 90° C., then ultrasonically dispersing, beating, kneading, extruding and forming, and then, under nitrogen protection, firstly using a microwave with a radiation frequency of 840 MHz to form a strip. The method comprises the steps of: drying, controlling the microwave drying temperature to be 100-120° C., and then drying with a microwave having a radiation frequency of 2450 MHz, controlling the microwave drying temperature to be 350-600° C., to obtain a sulfide-type bulk hydrogenation catalyst; wherein the molar amount of the ammonium dithiocarbamate used is 50%-300% of the molar amount of the nickel salt and / or the cobalt salt; and the sulfide-type bulk hydrogenation catalyst, based on the weight of the final catalyst, contains 30wt%-60wt% of molybdenum and / or tungsten in terms of elements, and 1wt%-15wt% of cobalt and / or nickel in terms of elements.

2. The method for preparing a sulfided bulk hydrogenation catalyst according to claim 1, characterized in that: The molar amount of the ammonium dithiocarbamate used is 100% to 150% of the molar amount of the nickel salt and / or the cobalt salt.

3. The method for preparing a sulfided bulk hydrogenation catalyst according to claim 1, characterized in that: The nickel salt and / or cobalt salt is selected from one or more of basic carbonate, nitrate and acetate.

4. The method for preparing a sulfided bulk hydrogenation catalyst according to claim 1, characterized in that: The adhesive is one or more of aluminum sol, silica sol, aluminum silicate and silica-alumina gel.

5. The method for preparing a sulfided bulk hydrogenation catalyst according to claim 1, characterized in that: The microwave sensitizer is one or more of Fenton's reagent, activated carbon, graphite, conductive carbon black, semi-conductive carbon black and carbon fiber sensitizer.

6. The method for preparing a sulfided bulk hydrogenation catalyst according to claim 1, characterized in that: The dispersant is one or more of alkylamide compounds, polycarboxylic acids, oligomers composed of polycarboxylic acids and polyamines, triethylhexyl phosphoric acid, alkyl sulfates, alkyl sulfonates, methyl amyl alcohol, cellulose derivatives, polyacrylamide, gum, silicates, polyethylene wax, oxidized polyethylene wax, polyethylene glycol, polyvinyl alcohol, polypropylene alcohol, isopropanol, sec-butyl alcohol, ethylene-vinyl acetate copolymer, fatty acid compounds, ester compounds, paraffin, polyurethane, fatty alcohol polyoxyethylene ether, and alkylphenol polyoxyethylene ether, and the amount used is 1wt%~20wt% of the weight of the carrier component.

7. The method for preparing a sulfided bulk hydrogenation catalyst according to claim 1, characterized in that: The ultrasonic time is 5 to 30 minutes.

8. The method for preparing a sulfided bulk hydrogenation catalyst according to claim 1, characterized in that: The 840 MHz microwave drying time is 10 to 30 minutes; the 2450 MHz microwave drying time is 20 to 120 minutes.

9. A sulfided bulk hydrogenation catalyst prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Unsupported catalyst and preparation method thereof

    CN101255356A

  • Hydrogenation catalyst composition, preparation method and use thereof

    CN101306374A

  • Hydrotreating catalyst and preparation method thereof

    CN102049265A

  • Preparation method of hydrogenation catalyst composition

    CN102451703A

  • A catalyst composition and preparation method thereof

    CN1951561A